Drying-induced physico-chemical changes in cranberry products. (1st February 2018) - Michalska, Anna; Wojdyło, Aneta; Honke, Joanna; Ciska, Ewa; Andlauer, Wilfried
Highlights: Cranberry powders were examined in terms of physico-chemical properties. Formulation of cranberry juice strongly affected the content of polyphenols in powders. Formation of hydroxymethylfurfural was accelerated by chlorogenic acid. 2-Furoylmethyl-amino acids were present in all cranberry juice powders. Antioxidant capacity was correlated with polyphenols content. Abstract: Sugar-free cranberry juice (XAD) and juice with 15% of maltodextrin were dried by freeze-, vacuum and spray drying methods. Total phenolics (589–6435 mg/kg dry matter) including 5 flavonols, 3 phenolic acids, 2 procyanidins and 5 anthocyanins were stronger affected by juice formulation than by drying methods. Spray drying of juice, regardless of its formulation, was competitive to freeze drying in terms of polyphenols' retention. Increase in temperature up to 100 °C during vacuum drying of XAD extracts resulted in degradation of polyphenolics (down to 4%), except chlorogenic acid. Its content increased with rise in temperature and accelerated hydroxymethylfurfural formation. The stronger the impact of drying, the more chlorogenic acid is present in cranberry products. In all powders analysed, formation of furoylmethyl amino acids was noted. Antioxidant capacity of cranberry products was influenced by juice formulation and was linked to content of polyphenols.